LIFE JOURNEY: MEDICAL AND SCIENTIFIC WORK OF PROFESSOR V.A. SOKOLOV - P. A. Ivanov; A. M. Fain; M. V. Sychevsky (Неотложная медицинская помощь, 2017)
The article is dedicated to doctor of medicine, professor V.A. Sokolov. In 2017 he celebrates his eightieth birthday. Professor V.A. .Sokolov is one of the founders of polytrauma treatment in USSR and Russia. For a long time he had been heading polytrauma department at the N.V. Sklifosovsky Research Institute for Emergency Medicine. Due to his work, algorithms of life sustaining and recovery of serious patients were developed. Professor V.A. Sokolov is the author of 6 monographies and about 300 periodical papers. Besides, he is the holder of 32 patents. Some of his inventions were popularized and manufactured. He had been leading active scientific work, which resulted in 6 doctoral dissertations and 15 candidate theses. The staff of N.V. Sklifosovsky Research Institute for Emergency Medicine congratulates on the anniversary.